Empowering the Creative Economy of PKK Women through Asset-Based Community Development (ABCD): Innovation in Cassava Wingko and Handmade Crafts - Moh Ali Fauzi; Melinda Ade Prastiwi; Nurani Rahmania (STAI Miftahul ULa Nganjuk, 2025)
This article discusses a community empowerment program aimed at enhancing the creative economy of Pamilya Welfare Empowerment (PKK) women in Senggowar Village. The program was driven by the issue of underutilized local economic potential. Using the Asset-Based Community Development (ABCD) approach, the initiative focused on identifying and optimizing existing local assets, including raw materials (abundant cassava and leftover fabric) and human resources (the PKK women's group). The implementation involved training and mentoring in creating innovative products cassava-based wingko (a traditional snack) and handmade crafts (scrunchies and doormats). The results show the successful creation of new, marketable products and the development of the participants' skills. This empowerment model successfully triggered increased family economic independence by opening up new business opportunities based on village potential. The program demonstrates that a strengths-based approach can effectively unlock local economic potential and encourage community self-sufficiency